Playing level and playing position differences of anthropometric and physical fitness characteristics in elite junior handball players - Rousanoglou, E. N.; Noutsos, K. S.; Bayios, I. A. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The purpose of the study was to identify the playing level (Under 16: U16, Under 18: U18 and Under 20: U20) and the playing position (Goalkeepers, Backs, Wings, Pivots, Centers) differences of elite junior handball players expressed in the anthropometric and physical fitness characteristics.